Assessment of Freshwater Quality in Endau Area - M. N., Mat Hassan; Norhidayah, Abdull (Universiti Malaysia Pahang, 2013)
Water Quality Index (WQI) uses as a basis for the assessment of a watercourse in relation to pollution load categorization. It designs the classes of beneficial uses of river as stipulated in Intern National Water Quality Standards for Malaysia (INQWS). In this study, the current status of fresh water in the Endau area (Sungai Anak Endau, Sungai Mok and well) was determined by measuring the physicochemical parameters (chemical oxygen demand, total suspended solid, biochemical oxygen demand, ammoniacal nitrogen, pH and dissolved oxygen). The finding of this study shows that all sampling stations for fresh water at Endau were in class II which has read in the range of 76.5% to 92.7%. According to INQWS River Classification indicates that water class II can be used for public consumption but conventional treatment required. Therefore, the application of WQI can be an effective guideline to the residents on assessing the overall quality of freshwater.